Chlorine removal from the pyrolysis of urban polyolefinic waste in a semi-batch reactor. Issue 1 (February 2021) - Torres, D.; Jiang, Y.; Sanchez Monsalve, D.A.; Leeke, G.A.
Abstract: The pyrolysis of urban chlorine-containing polyolefinic plastic waste with simultaneous retention of HCl is investigated. Different chemical removers based on sodium, calcium and zinc bases, and different adsorbents based on alumina or zeolites were used inside the reactor or in downstream hot filters, respectively, for chlorine removal and upgrading of pyrolysis oils. Initially, polyolefin waste (POW, containing a 98.5 wt% polyolefins) was thermogravimetrically pyrolyzed to determine its thermal behaviour. Subsequently, chemical removers were mixed with the POW which was pyrolyzed at 480 °C in a semi-batch reactor. The adsorbents were tested separately in hot filters (300 ± 20 °C) downstream of the pyrolysis reactor. After the pyrolysis, the resulting char containing the chemical removers and the absorbents in the hot filters were analysed by FTIR, CHN elemental analysis and ESEM-EDS to determine their respective chlorine contents. The highest chlorine retention was 23.8 wt% for chemical remover when used in direct contact with POW, while a zeolite used in the hot filter (gas streams) gave a chlorine retention of 65.6 wt%. The pyrolytic liquids consisted of mixtures of C7 -C40 hydrocarbons made up of olefinic and aliphatic hydrocarbons with a very low presence of aromatics (estimated to be below 3 wt% by HPLC). In most cases, the chlorine removal processes resulted in waxier pyrolytic oils and with a higher degree of branching. Graphical Abstract: ga1 Highlights: The pyrolysis of urban plastic waste with simultaneous retention of HCl is studied. Chemical remover/waste mixtures are pyrolyzed in a semi-batch reactor. Adsorbents are tested in hot filters downstream of the pyrolysis reactor. Chars are analysed by elemental analysis and ESEM-EDS to known the Cl retention. Pyrolytic liquids are mixtures of C7 -C40 olefinic and aliphatic hydrocarbons.